Cannabis use and patterns among middle and older aged Canadians prior to legalization: a sex-specific analysis of the Canadian Tobacco, Alcohol and Drugs Survey - Asvini Keethakumar; Vrati M. Mehra; Nazilla Khanlou; Hala Tamim (BMC, 2021)
Abstract Background The recreational use of cannabis was legalized across Canada in October 2018. While many people use cannabis without harm, adverse outcomes have been noted in a few populations, including middle-aged and older adults. Given that the current literature has neglected to study cannabis use among this population and between sexes, the objective of our study was to identify the prevalence, characteristics, and patterns of cannabis use among middle and older aged males and females prior to legalization in Canada. Methods Secondary analysis was conducted on the Canadian Tobacco, Alcohol and Drugs Survey 2017, with the sample restricted to adults ages 40 and above. The main outcome was defined as past-year cannabis use and statistical analysis was conducted separately for males and females. Bivariate and multivariable logistic regression was performed to identify associations between the main outcome and various sociodemographic, health, and substance use variables. Explanatory supplementary variables were also explored. Results In 2017, 5.9% of females and 9.0% of males over the age of 40 reported past-year cannabis use. Almost 62% of males who used cannabis in the past-year reported a failed attempt at reducing or stopping their cannabis use. Over half (56%) of older females, self-reported using cannabis for medical purposes. Additionally, over one in five older adults reported using a vaporizer or e-cigarette as a delivery method for cannabis. Significant characteristics of male cannabis use included having no marital partner, cigarette smoking, and illegal drug use. Furthermore, significant predictors of past-year cannabis use in females included residing in an urban community, Eastern- Atlantic provinces or British Columbia, having fair/poor mental health, smoking cigarettes, use of other tobacco products, and illegal drugs. Conclusion To our such knowledge, this is the first nationally representative study to outline the prevalence, characteristics, and patterns of past-year cannabis use prior to Canadian legalization, among middle and older aged Canadians. Results from this study are expected to be used to reliably to track changes in usage, behaviours, and related disorders in the years to come.